Principles Of Compassion In The World Religions For Coexistence Among Religions In The Perspective Of Karen Armstrong - Supriyanto Supriyanto (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2022)
Abstract Sociologically, the face of human life on this earth is pluralistic, not only in culture, language, ethnicity, customs, skin color and ethnicity, but also in aspects of religious beliefs. The problem is, the plurality of religious beliefs colored by clash after clash between various adherents of different religions. In modern history, there have been so many violent conflicts and acts of terrorism that have occurred in the name of faith in various parts of the world. Although various motives other than religion can be sought, the perpetrators of modern terrorism claim to be inspired and motivated by a certain understanding of religion. Karen Armstrong presents a brilliant offer to the conflict that must be sought for a common platform that is fundamental and lies at the heart of every tradition of the world's major religions such as Islam, Judaism, Christianity, Hindi, Buddhism, and Confucianism. Karen found a fundamental principle that could become a common platform among world religions, namely the principle of compassion. This article will discuss Karen Armstrong's thoughts on the principles of compassion in the world's religious traditions for inter-religious coexistence using a historical and philosophical critical approach in depth. Keywords: Compassion, World religion, coexistence, Karen Armstrong Abstrak Secara sosiologis, wajah kehidupan umat manusia di muka bumi ini berbentuk pluralistik bukan hanya dalam budaya, bahasa, etnis, adat, warna kulit dan suku bangsa, melainkan juga dalam aspek keyakinan agama. Persoalannya, pluralitas keyakinan agama tersebut tidak jarang diwarnai dengan benturan demi benturan antara pelbagai penganut agama yang berbeda satu sama lain. Dalam sejarah modern ini, terdapat begitu banyak konflik kekerasan dan tindakan terorisme yang terjadi atas nama keyakinan diberbagai belahan dunia. Meskipun bisa dicari pelbagai motif-motif selain agama, para pelaku terorisme modern tersebut mengaku diilhami dan dimotivasi oleh pemahaman tertentu atas agama. Karen Armstrong menyuguhkan sebuah tawaran brilian terhadap konflik tersebut bahwa harus dicari sebuah common flatform (pijakan bersama) yang bersifat fundamental dan terletak dalam jantung setiap tradisi agama-agama besar dunia seperti Islam, Yahudi, Kristen, Hindi, Buddha, dan Kong Hu Cu. Karen menemukan sebuah prinsip fundamental yang bisa menjadi common flatform antar agama-agama dunia yakni prinsip belas kasih (compassion). Artikel ini akan mendiskusikan pemikiran Karen Armstrong tentang prinsip-prinsip belas kasih dalam tradisi agama-agama dunia bagi koeksistensi antar umat beragama dengan menggunakan pendekatan historis dan dan kritis filosofis secara mendalam. Kata Kunci: Belas kasih, Agama dunia, koeksistensi, Karen Armstrong